The Speed of Adjustment to the Target Market Value Leverage Is Slower Than You Think - Yin, Qie Ellie; Ritter, Jay R. (Journal of Financial and Quantitative Analysis, 2020)
In the capital structure literature, speed of adjustment (SOA) estimates are similar whether book or market leverage is used. This robustness is suspect, given the survey evidence that firms target their book leverage and the empirical evidence that they don’t issue securities to offset market leverage changes caused by stock price changes. We show that existing market SOA estimates are substantially upward biased due to the passive influence of stock price fluctuations. Controlling for this bias, the SOA estimate is 16% for book leverage and 10% for market leverage, implying that the trade-off theory is less important than previously thought.